INNOVATIONS AS A DIRECTION OF IMPROVING THE EFFICIENCY OF GRAIN PRODUCTION - Сулима, Наталья (SWorldJournal, 2021)
The paper considers the dynamics of the level of production and economic efficiency of grain production in agricultural enterprises, as well as ways to increase them through innovative development of the industry.